Similar but Superior: Rhetoric of Coexistence Employed by Religions in Jeju Island, Korea - Yohan Yoo (Religions, 2020)
Religions in Jeju, South Korea, have sometimes been in conflict with each other, but have generally coexisted peacefully. In a situation where diverse religions share an island that is isolated from the mainland, they have emphasized that they are similar yet superior to their rivals. Religions that were imported to Jeju, including Confucianism, Buddhism, and Christianity, have tried to make themselves look familiar to Jeju people on the basis of people’s knowledge of preexisting religions. These religions sometimes embraced rituals of preexisting religions to which people were strongly attached. The Jeju indigenous religion has also acknowledged that the ideas and practices of Buddhism and Confucianism have remarkable similarities to those of its own. Simultaneously, each religion in Jeju has claimed its superiority over others. Religions in Jeju have argued that other religions’ partial truth and limited value are in sharp contrast with the complete truth and superior value of their own. They have asserted that only they can provide the proper way of keeping the order of the universe or attaining salvation of human beings. This common rhetoric that “my religion is similar but superior to other religions” has been repeated in Jeju, in order to persuade people outside the religion to accept or at least approve it on the one hand, and to maintain the peaceful coexistence with other religions on the other hand.